Growth Response of Pinus wallichiana to Changing Climate in Temperate Regions of Central Nepal - Shiwakoti, Tulasi; Thapa, Nita; Basnet, Saroj; Tiwari, Achyut (Journal of Plant Resources, 2022)
Climate influences both the structure and function of the forest ecosystem. A dendrochronological study was carried out in temperate forest at Patney Bhanjyang Community Forest of Kavrepalanchok district in Central Nepal to verify and record the impact of climate on radial growth by using the tree cores of Pinus wallichiana. A total of 60 tree cores were collected by using increment borer and annual ring widths were analyzed by using the standard dendrochronological technique. We produced a 74-year-old tree ring width chronology of P. wallichiana from the region and examined the critical climatic factor for radial growth and the temporal trend of Basal Area Increment (BAI). Our results showed that the tree radial growth was not influenced by maximum temperature. However, it was positively correlated with the minimum temperature of the previous year September (0.30) indicating that cool previous September is favorable for radial growth. Similarly, the radial growth of Pine showed a positive correlation with the total rainfall of January (0.33) and March (0.33), showing that enough moisture in the very early growing season contributes positively to radial growth. We found a decline in BAI after 2000 AD until 2005, although BAI was relatively stable despite the decreasing trend of rainfall. We did not find the impact of climatic factor for the decline in BAI. However long-term study of different climatic, ecological and anthropogenic influences are necessary to know more about the growth–climate relationship of P. wallichiana in temperate forests of Nepal.